2021
DOI: 10.14336/ad.2020.0704
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Endovascular Therapy for Basilar Artery Occlusion: Intracranial Atherosclerotic Disease vs. Embolism

Abstract: Acute ischemic stroke due to basilar artery occlusion (BAO) carries a very poor prognosis. Functional outcomes in BAO patients undergoing endovascular therapy (EVT) may differ according to the specific pathological mechanisms. We aimed to explore the impact of the underlying pathological mechanisms on prognosis at 90-days and long-term follow-up in BAO patients treated with EVT. We analyzed consecutive BAO patients undergoing EVT from December 2012 to December 2018 at a single center (Xuanwu Hospital). Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
(55 reference statements)
2
26
1
1
Order By: Relevance
“…Intraprocedural use of glycoprotein IIb/IIIa inhibitor, percutaneous transluminal angioplasty, or stenting for underlying intracranial stenosis as rescue therapy was shown to improve the rate of functional outcome. With the use of rescue therapy, there was no significant difference in the rates of favorable outcome between in situ atherosclerotic thrombosis group and embolic group (26.9% vs. 33.7%, 37.5% vs. 41.5%, or 60% vs. 51%, respectively) [26,55,57].…”
Section: Rescue Therapymentioning
confidence: 92%
See 4 more Smart Citations
“…Intraprocedural use of glycoprotein IIb/IIIa inhibitor, percutaneous transluminal angioplasty, or stenting for underlying intracranial stenosis as rescue therapy was shown to improve the rate of functional outcome. With the use of rescue therapy, there was no significant difference in the rates of favorable outcome between in situ atherosclerotic thrombosis group and embolic group (26.9% vs. 33.7%, 37.5% vs. 41.5%, or 60% vs. 51%, respectively) [26,55,57].…”
Section: Rescue Therapymentioning
confidence: 92%
“…Due to poor natural history, significant numbers of patients with acute BAO were treated with EVT empirically worldwide in the last 2 decades. Eighteen published retrospective studies were found to have sample size ≥ 100 and functional outcome data at 90 days [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In these studies, most patients had median or mean National Institutes of Health Stroke Scale (NIHSS) scores 14-31.…”
Section: Retrospective Studiesmentioning
confidence: 99%
See 3 more Smart Citations